Heart rate recovery is associated with ventilatory constraints and excess ventilation during exercise in patients with chronic obstructive pulmonary disease. (29th August 2020) - Crisafulli, Ernesto; Vigna, Matteo; Ielpo, Antonella; Tzani, Panagiota; Mangia, Angelo; Teopompi, Elisabetta; Aiello, Marina; Alfieri, Veronica; Bertorelli, Giuseppina; Palange, Paolo; Chetta, Alfredo
Abstract: Background: Heart rate recovery delay is a marker of cardiac autonomic dysfunction. In chronic obstructive pulmonary disease patients, the ventilatory response to exercise during incremental cardiopulmonary exercise test may add information about dynamic hyperinflation by low values of inspiratory capacity/total lung capacity ratio (at peak) and excess ventilation by the slope of minute ventilation to carbon dioxide output ratio (VE /VCO2 slope ). We aimed to assess if the ventilatory response to exercise might be a determinant for heart rate recovery delay. Design: An observational, prospective study. Methods: Anthropometric characteristics, lung function and cardiopulmonary exercise test data were recorded in chronic obstructive pulmonary disease outpatients. A cut-off of heart rate recovery of 12 or more beats was used to define heart rate recovery delay. Results: Of 254 patients enrolled, 156 (61%) showed heart rate recovery delay. As compared to patients with normal heart rate recovery, patients with delay were older, with a worse lung function and with lower values of peak oxygen uptake, maximal workload, oxygen pulse at rest and at peak, and inspiratory capacity/total lung capacity at peak. Conversely, VE /VCO2 slope and dyspnoea and leg fatigue perception at peak were higher in patients with heart rate recovery delay. In the multivariate regression model adjusted for age, sex, fat-free mass, heart rate at rest and use of β-blockers, we found that inspiratory capacity/total lung capacity at peak (<0.25) (odds ratio 2.61; P  = 0.007) and VE /VCO2 slope (>32) (odds ratio 2.26; P  = 0.018) predict the risk of heart rate recovery delay. Conclusions: In chronic obstructive pulmonary disease outpatients, heart rate recovery is associated with dynamic hyperinflation and excess ventilation during exercise.